Platelet Mitochondrial Dysfunction is Evident in Type 2 Diabetes in Association with Modifications of Mitochondrial Anti-Oxidant Stress Proteins - Avila, C.; Huang, R. J.; Stevens, M. V.; Aponte, A. M.; Tripodi, D.; Kim, K. Y.; Sack, M. N. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Mitochondrial dysfunction and oxidative stress in insulin responsive tissues is implicated in the pathogenesis of type 2 diabetes. Whether these perturbations extend to other tissues and contribute to their pathophysiology is less well established. The objective of this study was to investigate platelet mitochondria to evaluate whether type 2 diabetes associated mitochondrial dysfunction is evident in circulating cells.A pilot study of mitochondrial respiratory function and proteomic changes comparing platelets extracted from insulin sensitive (n=8) and type 2 diabetic subjects (n=7).In-situ platelet mitochondria show diminished oxygen consumption and lower oxygen-dependent ATP synthesis in diabetic vs. control subjects. Mass spectrometric identification and confirmatory immunoblot analysis identifies induction of the mitochondrial anti-oxidant enzymes superoxide dismutase 2 and thioredoxin-dependent peroxide reductase 3 in platelets of diabetic subjects. As oxidative stress upregulates anti-oxidant enzymes we assessed mitochondrial protein carbonylation as an index of oxidative-stress. Platelets of diabetic subjects exhibit significantly increased protein carbonylation compared to controls.As platelets are anuclear fragments of megakaryocytes, our data suggest that the bone marrow compartment in type 2 diabetic subjects is exposed to increased mitochondrial oxidative stress with upregulation of nuclear-encoded antioxidant mitochondrial enzymes. This ‘stress-signature’ in platelets of diabetic subjects is associated with a diminution of their mitochondrial contribution to energy production and support that mitochondrial perturbations in type 2 diabetes extends beyond the classical insulin responsive tissues. Platelets, as “accessible human tissue”, may be useful to measure the mitochondrial modulatory effects of emerging anti-diabetic therapeutics.
Keywords: mitochondria; platelets; reactive oxygen species; respiration; diabetes